2022
DOI: 10.3390/ijms232213827
|View full text |Cite
|
Sign up to set email alerts
|

May Sulfonamide Inhibitors of Carbonic Anhydrases from Mammaliicoccus sciuri Prevent Antimicrobial Resistance Due to Gene Transfer to Other Harmful Staphylococci?

Abstract: Mammaliicoccus sciuri, previously known as Staphylococcus sciuri, is a Gram-positive bacterium involved in gene transfer phenomena that confer resistance to multiple antibiotics. These plasmid-encoded genes can be easily transferred to other pathogenic staphylococci. Because antibiotic resistance is rising, inhibiting M. sciuri proliferation may be a credible strategy for restricting antimicrobial resistance gene transfer to other pathogenic bacteria. Recently, it has been shown that blocking bacterial carboni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The inhibition constants were obtained by non-linear least-squares methods using PRISM 3 and the Cheng-Prusoff equation, whereas the kinetic parameters for the uninhibited enzymes from Lineweaver-Burk plots, as reported earlier 21–23 , and represent the mean from at least three different determinations. MscCAγ was obtained as reported earlier 19 and its concentration in the assay system was of 12.6 nM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition constants were obtained by non-linear least-squares methods using PRISM 3 and the Cheng-Prusoff equation, whereas the kinetic parameters for the uninhibited enzymes from Lineweaver-Burk plots, as reported earlier 21–23 , and represent the mean from at least three different determinations. MscCAγ was obtained as reported earlier 19 and its concentration in the assay system was of 12.6 nM.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported 19 the cloning, purification and initial characterisation of a γ-class CA from the Gram-positive bacterium Mammaliicoccus sciuri (previously known as Staphylococcus sciuri ), MscCAγ, which is responsible of infections in humans and various other wild/domestic animals, but also of gene transfer phenomena to other bacteria, that confer drug resistance to multiple antibiotics 19 . We hypothesised 19 that inhibition of this enzyme may lead to a novel strategy for limiting the spread of multidrug resistance and investigated a range of sulphonamides and sulfamates as MscCAγ inhibitors. Some sulphonamides were indeed rather effective inhibitors, but compounds with an optimal selectivity profile for inhibiting the bacterial over the human enzymes have not yet been detected so far.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the druggability of CAs present in pathogens as novel anti-infective agents is becoming more and more appealing for design drugs with a novel mechanism of action. Indeed, these enzymes are essential in the life cycle (pH homeostasis and biosynthetic reactions) as well as in the virulence of many bacterial, fungal and protozoan pathogens and, several literature data have shown that their inhibition impairs parasite growth and virulence 44 . In this context, sulphonamide derivatives were studied and screened to obtain such novel anti-infective agents 45 , 46 .…”
Section: Click Chemistry To Develop Novel Cais As Anti-infective Agentsmentioning
confidence: 99%
“…A relevant number of papers dealing with this enzyme, its inhibitors, activators and involvement in various diseases have been published in 2022 in this journal [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The first group of contributed materials dealt with the use of this protein for investigations of basic biochemical approaches, such as protein folding [ 7 ], thermodynamic parameters assessment for protein–ligand interactions [ 8 ], bioluminescence resonance energy transfer connected to the binding of the metal ion to apoenzymes [ 9 ], the possibility to evidence chalcogen bonds in the X-ray crystal structures of CA–lig and adduct [ 10 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…A large number of CA-related papers dealt with the drug design of CA inhibitors (CAIs) with various applications as anticancer agents (both for treatment and imaging) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], antineuropathic pain compounds [ 20 ], mountain sickness leads [ 21 ], antiglaucoma agents [ 22 ] or antibacterials with a novel mechanism of action which, unlike classical antibiotics, target bacterial CAs from various pathogens [ 23 , 24 , 25 ]. Both sulfonamide and non-sulfonamide compounds have been reported in these interesting papers, which highly enrich the number of such pharmacological agents useful for the management of a multitude of pathological conditions [ 2 , 3 ].…”
Section: State Of the Artmentioning
confidence: 99%